Uzbekistan Folk Medicine Healing Morocco ( Salvia Insignis) Plant Significance - Nasirov Saidahror Shuxrat o’g’li (Zien Journals, 2022)
In this article shows that growth of curative mawrak(salvia) in accordance with climate condition of termiz that they are fully adopted to local condition.
Keywords: medicinal salvia officinalis; growth; development; number of seed